Revolución y amnistía en Argentina. La definición de las esferas civil y militar en el levantamiento radical de febrero de 1905 - María Laura Reali (Amnis)
The cycle of armed uprisings, which took place in Argentina between 1890 and 1905, was perceived and legitimized by its stakeholders as an alternative form of political participation and, up to some extent, as a « complementary » way of electoral struggle. More precisely, the banner of right to rebellion against governments lacking legitimacy –either by its origins or by its ways of functioning– was hoisted to justify armed actions that were self-defined as « revolution ». Political violence used to find a frame of legitimacy that was not alien to amnesty measures that used to follow the repressive actions applied against the defeated revolutionaries. Through this lens, it is possible to analyze a set of key problems of the first centenary of Argentina: issues such as social order, controversy over the traditional call to arms in the context of a State that pretended to be progressist and modern, the role of the armed forces between disciplinary and political engagement, transformations of the judiciary system –and in particular the military justice–, the qualification of crimes and the perception of the adversary. A preliminary analysis over some of these issues will be presented, with a focus on the radical revolution of 1905.